Determinants of Banten Young People's Intention to Pay Waqf Through Digital Platforms - Najib, Mohamad Ainun; Sujatna, Yayat (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The potential for cash waqf in Banten reaches IDR 55 billion per month or IDR 667.2 billion per year, but the realization is still far from expectations. One of the factors is related to the low literacy of the community, especially generation Y and Z about waqf. In a survey conducted by the Indonesian Waqf Board, the waqf literacy index score of Banten province in 2020 was 45.47 and the Waqf Basic Understanding Index Score was 50.88, this figure is in the low category. This study aims to determine the factors that influence the intention of Banten young people to donate through digital platforms, by adopting the concept of the Theory of Planned Behavior (TPB) which consists of subjective norms, perceived behavioral control, behavioral attitudes plus reliability and their influence on the intention to donate. This study uses an associative quantitative approach, the analysis was carried out using Structural Equation Modeling (SEM) with the SmartPLS application tool to test seven hypotheses of the relationship between variables in the model. Respondents, as many as 124 people were selected through a purposive sampling technique to get Muslim respondents interested in waqf through digital platforms. The results showed that subjective norms do not have a positive effect on behavioral intentions, perceived behavioral control has a positive and significant effect on behavior intention, religiosity has a significant positive effect on behavioral intention, attitude has a significant positive effect on behavioral intention. This study implies the need to improve their understanding through more intensive education and counseling, and the use of digital platforms that can facilitate access, transparency, and trust, developing and promoting digital platforms that are easily accessible, user-friendly, and secure. a more personalized approach in waqf campaigns, which emphasizes the religious aspects and direct benefits of waqf itself, to encourage waqf intentions. Potensi wakaf uang tunai di Banten mencapai Rp55 miliar per bulan atau Rp. 667,2 miliar per tahun, tetapi pada realisasinya masih jauh dari harapan. Salah satu faktornya terkait literasi masyarakat khususnya generasi Y dan Z tentang wakaf masih rendah, Dalam survey yang dilaksanakan Badan Wakaf Indonesia skor indeks literasi wakaf provinsi Banten pada Tahun 2020 diangka 45,47 dan Skor Indeks Pemahaman Dasar Wakaf mendapatkan angka 50.88, angka tersebut masuk dalam kategori rendah. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi niat anak muda Banten untuk berwakaf melalui platform digital, dengan mengadopsi konsep Theory of Planned Behavior (TPB) yang terdiri dari norma subyektif, kontrol perilaku yang dipersepsikan, sikap perilaku ditambah dengan keandalan dan pengaruhnya terhadap niat berdonasi. Penelitian ini menggunakan pendekatan kuantitatif asosiatif, analisis dilakukan dengan menggunakan Structural Equation Modeling (SEM) dengan alat bantu aplikasi SmartPLS untuk menguji tujuh hipotesis hubungan antar variabel dalam model. Responden sebanyak 124 orang dipilih melalui teknik purposive sampling untuk mendapatkan responden muslim yang tertarik berwakaf melalui platform digital. Hasil penelitian menunjukkan bahwa norma subjektif tidak berpengaruh terhadap niat berperilaku, kontrol perilaku yang dipersepsikan berpengaruh terhadap niat berperilaku, religiusitas berpengaruh terhadap sikap niat berperilaku, sikap berpengaruh positif signifikan terhadap niat perilaku. Penelitian ini mengimplikasikan perlu meningkatkan pemahaman mereka melalui pendidikan dan penyuluhan yang lebih intensif, dan penggunakan platform digitalyang bisa mempermudah akses, transparansi, dan kepercayaan, mengembangkan dan mempromosikan platform-platform digital yang mudah diakses, user-friendly, dan aman. pendekatan yang lebih personal dalam kampanye wakaf, yang mengedepankan aspek religiusitas dan manfaat langsung dari wakaf itu sendiri, untuk mendorong niat berwakaf.